Evaluation of Azolla Compost as Bio-fertilizer in Carp Culture - Ansal, M.D.; Kaur, K.; Kaur, V.I. (Indian Journal of Animal Nutrition, 2018)
Efficacy of Azolla compost (AC), as bio-fertilizer in carp culture, was evaluated through a 150 days grow out trial in cemented tanks stocked with common carp fry (BW-0.60-0.61g) @ 50,000/ha. The study comprised of four treatments and three replicates per treatment, where cow dung (CD), AC and CD +AC combinations (CD+AC, 1: 1 and CD+AC, 1: 3) were used to manure the tanks. The tank manured with CD served as control. In all the treatments, the manure was added at the rate of 20,000 kg/ha/yr, where Â¼th of the dose was added 15 days prior to stocking of fish, while rest of the manure was added in equal doses every week. Better water quality in terms of dissolved oxygen (DO) and ammonia content was observed in AC treatments. Significantly higher DO content (P<0.05) was recorded in both the CD+AC combination (1: 1 and 1:3 ) treatments (5.31 and 5.11 mg/L, respectively) and AC treatment (5.72 mg/L), as compared to control treatment CD (3.87 mg/L). Ammonia levels were lower (P<0.05)) in CD+AC (1: 3) combination (0.039 mg/L) and AC treatment (0.037 mg/ L),as compared to CD (0.058 mg/L). Further, a higher (P<0.05) zooplankton population was also recorded in CD+AC combination (1: 1 and 1: 3) and AC treatments which revealed overall positive effect of AC on the ecology of the culture system. The Maximum phytoplankton (706 Ã—106/L) and zooplankton (1812/L) populations were, however, recorded in CD+AC (1: 3) treatment. Survival of fish was above 90% (91.60 to 93.75%) in all the treatments. The fish growth was higher (P<0.05) in terms of net weight gain (NWG) in CD+AC (1: 3 and 1: 1) treatments (35.58 g and 32.55 g) which was 25.28% and 14.61% higher than NWG (28.40 g) in control. The study revealed that AC can be used as a potential biofertilizer,either alone or in combination with CD (CD+AC, 1: 3) for higher fish growth and productivity in carp culture.